Dry matter accumulation of maize hybrids under different source:sink ratios - Sangoi, Luís; Lech, Vanderlei Adilson; Rampazzo, Clair; Gracietti, Luís Carlos (Pesquisa Agropecuaria Brasileira, 2002)
Little attention has been given to the study of phenological and physiological differences among contrasting cycle maize hybrids during grain filling. This experiment was conducted in order to evaluate the effects of planting density and defoliation on dry matter accumulation after flowering of maize hybrids with different thermal requirements to reach tasseling. The trial was performed in Lages, SC, Brazil. Two hybrids were tested: P32R21, very early, and C333B, late, at four plant populations: 25,000, 50,000, 75,000 and 100,000 plants/ha. Dry matter accumulation was estimated at 0, 21, 42 and 64 days after anthesis. Plants were assessed with intact leaf area and having half of their green leaves removed at anthesis. The very early hybrid presented greater speed of grain dry matter accumulation and higher decrease of leaf dry matter 64 days after anthesis than the late hybrid. Hybrid C333B showed lower dry matter accumulation rates during the first three weeks after anthesis than at the end of the filling grain period. Increase in plant population and defoliation reduced grain dry matter accumulation rates of both hybrids.